¿De la tutela a cuál autonomía? Reflexiones sobre la auto-determinación indígena en Brasil - Lamounier, Alice (2012)
In recent decades significant changes on indigenous autonomy are the result of the struggles of indigenous movements in Brazil. The legal instruments prior to 1988 were characterized by the tutelage of indigenous people, a situation that changes in the new legal frameworks. In practice several different experiences of self support begin to emerge.